2015
DOI: 10.1016/j.bbamem.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid modulation of early G protein-coupled receptor signalling events

Abstract: Upon binding of extracellular ligands, G protein coupled-receptors (GPCRs) initiate signalling cascades by activating heterotrimeric G proteins through direct interactions with the α subunit. While the lipid dependence of ligand binding has previously been studied for one class A GPCR, the neurotensin receptor 1 (NTS1), the role the lipid environment plays in the interaction of activated GPCRs with G proteins is less well understood. It is therefore of interest to understand the balance of lipid interactions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 72 publications
0
44
0
Order By: Relevance
“…Recently, we showed that binding of neurotensin to NTS1, receptor homodimerisation, and coupling to G αi1 are greatly affected by the specific lipid composition of the bilayer [40,41], and Grisshammer and co-workers showed that the same holds for G q protein activation [12]. Here, we now analyse how major lipid species of the mammalian plasma membrane interact with the transmembranous region of rat NTS1 using a fusion protein termed NTS1-B.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 83%
“…Recently, we showed that binding of neurotensin to NTS1, receptor homodimerisation, and coupling to G αi1 are greatly affected by the specific lipid composition of the bilayer [40,41], and Grisshammer and co-workers showed that the same holds for G q protein activation [12]. Here, we now analyse how major lipid species of the mammalian plasma membrane interact with the transmembranous region of rat NTS1 using a fusion protein termed NTS1-B.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 83%
“…Dijkmam et al . demonstrated that the class A GPCR neurotensin receptor 1, when incorporated into nanodiscs rich in phosphatidylethanolamine, experienced the Gα i1 subunit having a fourfold higher affinity for the GPCR. While various other GPCRs have been incorporated into nanodiscs to study their function (Table ), the effect of various lipid compositions on GPCR functionality has not been thoroughly investigated.…”
Section: Biophysical Studies Of Membrane Proteins In Nanodiscsmentioning
confidence: 99%
“…Sternweis and Robishaw reported thehigh affinity binding of a non-hydrolyzable GTP analog, GTPS, for G-protein in bovine brain membranes, with 0.37 nmol/mg of protein[73,74]. "Kinetic data on G protein activation are difficult to obtain,"[69], however, and parameters on the affinity between a GPCR and a G-protein have not clearly been reported so far, especially in cells[69], except for rhodopsin with Kd of nM ranges determined by cell-free, surface plasmon-waveguide resonance spectroscopy[75,76] and for a class A GPCR with Kd of around 100 nM by microscale thermophoresis[77]. A recent study, by double electron-electron resonance spectroscopy through paramagnetic labels carrying unpaired electrons that can be introduced commonly as nitroxides via usually sulfhydryl group of cysteine residues of proteins of interest[78], indicates "a minority population exhibiting substantial domain separation" between the GTPase and helical domains of G-protein [79], although "no crystal structure of a nucleotide-bound G protein has captured a domain-separated conformation-perhaps because such conformations are less populated and less amenable to crystallization than one with the domains in tight contact-"[80].…”
mentioning
confidence: 99%